Assessing the Performance of Nurses in the Standard Care of Airway and Oropharynx in Intensive Care Units of Ahwaz Golestan Hospital - Nader Hasanvand (Journal of Global Pharma Technology, 2017)
Maintaining an open airway is one of the fundamental steps in the patients and due to complications associated with non-standard and high sensitivity in ICU, this study aimed to evaluate the performance of nurses in standard care of airway and oropharynx in the intensive care units of Golestan hospital in Ahwaz. in this cross-sectional study, by the checklist of care standards of airway and oropharynx and a questionnaire,  demographic information of 72 nurses working in the intensive care unit in Ahwaz Golestan hospital in 2015 were measured after written consent in different working shifts. The validity of questionnaire was verified by the viewpoints of professors of nursing and its reliability by agreement between the present observers. Eventually, the data collected was analyzed using descriptive statistics and Kruskal-Wallis test, Mann Whitney U and Pearson correlation coefficients using SPSS version 20. Among the care standards, cleaning the lumen of the catheter has been a measure which has been undertaken by the majority of nurses (98/6 percent), while reviewing a medical history of possible problems in patients was observed only in 23.6% of the nurses. Overall mean of use of care standards of airway and oropharynx was 9/92 ± 81/60 respectively. Also significant positive relationship was observed between job characteristics and their performance in the care of the airways (05/0> P). Although in most cases the implementation of care was optimal, the implementation of the measures examined in the patient's medical history is not done properly. Hence, the importance of standard care in patients required more accurate monitor of the performance of staff and the necessary steps also should be taken to rectify the affecting factors.